2013
DOI: 10.1111/1556-4029.12301
|View full text |Cite
|
Sign up to set email alerts
|

Interpretation of Pharmaceutical Drug Concentrations in Young Children's Head Hair

Abstract: Three separate cases of child administration of prescription drugs are described. Following liquid-liquid extraction, high-performance liquid chromatography-tandem mass spectrometry (HPLC-MS/MS) was used to identify and quantify methadone, 2-ethylidene-1,5-dimethyl-3,3-diphenyl-1-pyrrolidine (EDDP), tramadol, amitriptyline, and nortriptyline in children's hair. The children's age ranged from 14 months to 7 years; in all three cases, the drug in question was detected in more than one section of hair. Methadone … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 22 publications
1
9
0
Order By: Relevance
“…The values obtained were consistent with results described in literature that presented values between non detected and 57.7 ng/mg for AMI and between 0.007 and 9.2 ng/mg for NOR (Table 5) [10][11][12][13][14][15][16][17][18][19].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The values obtained were consistent with results described in literature that presented values between non detected and 57.7 ng/mg for AMI and between 0.007 and 9.2 ng/mg for NOR (Table 5) [10][11][12][13][14][15][16][17][18][19].…”
Section: Discussionsupporting
confidence: 91%
“…More recently, Chatterton reported a case of kidnap and false imprisonment where AMI and NOR were evaluated in hair of the child between 0.007 and 0.318 ng/mg [10]. In another case, AMI was detected in the range of 0.18-1.06 ng/mg, while NOR was detected in the range of 0.38-2.0 ng/mg [11]. It was also reported that after a single dose, concentration of AMI was measured at 0.037 ng/mg [12].…”
Section: Discussionmentioning
confidence: 99%
“…Various analytical procedures have been reported in the literature to analyze TRAM and metabolites in the keratin matrix by GC-MS [14][15][16][17] and LC-MS [18][19][20][21][22]. Some authors present only the qualitative identification of TRAM in hair, without any quantitative data [19] and other authors quantify exclusively the parent drug TRAM [15,16,18].…”
Section: Introductionmentioning
confidence: 99%
“…Although no information was available on the administered dose, the analysis demonstrated a repeated administration of the drugs over a longer period. The second report presented three cases of administration of prescribed drugs to a child with one of the cases involving amitriptyline 18 . A mother, who had a prescription for amitriptyline, was accused of administrating amitriptyline to her children (7 and 12 years old) over a 6‐12‐month period.…”
Section: Case Reports and Reports Of Drug‐facilitated Crimesmentioning
confidence: 99%